Talent Identification and Development Programme (2002)
The review concludes by noting three main areas for attention. Research Research to date has been orthogonal. Researchers have confined themselves to relatively simplistic uni-dimensional examinations. Multi-factor longitudinal studies must become the norm with an inter-disciplinary approach essential in order to cater for the known interactions that occur in a multiplicative manner. It is arguable that no true TI schemes currently exist in Britain. Ongoing longitudinal research that tracks a number of youngsters to a number of factors appears to be required. Development and Potential Building The focus on current performance rather than potential is paralleled by the need for successful youth squads that drives the development agenda. Using empirical research, agencies could redirect their performance outcomes towards a more developmental and an agenda for potential building. The review calls for leadership in driving this work forward to influence the development of young people in sport. Potential Outcomes of Talent Identification and Development Schemes New approaches could be used to equip and empower young people for a lifetime of physical activity. For the health of talent identification and development and the long-term health of the nation talent development systems should be focused on the early development of motor capacity. It could help with: Potential building for performance sport. Raising physical activity levels. Identifying and providing initial rehabilitation for those with mild motor improvement. Also needed would be the development of a psychological excellence profile.